Time to decide about risk-reducing mastectomy: A case series of BRCA1/2 gene mutation carriers - Kelly Mary; Bottorff Joan L; McCullum Mary; Kieffer Stephanie A; Balneaves Lynda G (BMC, 2007)
Abstract Background The purpose of this research was to explore women's decision-making experiences related to the option of risk-reducing mastectomy (RM), using a case series of three women who are carriers of a BRCA1/2 gene mutation. Methods Data was collected in a pilot study that assessed the response of women to an information booklet about RM and decision-making support strategies. A detailed analysis of three women's descriptions of their decision-making processes and outcomes was conducted. Results All three women were carriers of a BRCA1/2 gene mutation and, although undecided, were leaning towards RM when initially assessed. Each woman reported a different RM decision outcome at last follow-up. Case #1 decided not to have RM, stating that RM was "too radical" and early detection methods were an effective strategy for dealing with breast cancer risk. Case #2 remained undecided about RM and, over time, she became less prepared to make a decision because she felt she did not have sufficient information about surgical effects. Case #3 had undergone RM by the time of her second follow-up interview and reported that she felt "a load off (her) mind now". Conclusion RM decision making may shift over time and require decision support over an extended period.